Perinatal asphyxia and its associated factors in Ethiopia: a systematic review and meta-analysis - Sendeku, Fikadu Waltengus (BMC Pediatr, 2020)
BACKGROUND: Despite different preventive strategies that have been implemented in different health institutions in the country, neonatal mortality and morbidity are still significantly increasing in Ethiopia. Perinatal asphyxia is the leading cause of neonatal morbidity and mortality worldwide. As a result, this systematic review and meta-analysis aimed to assess the prevalence and associated factors of perinatal asphyxia in Ethiopia. METHODS: Online databases (PubMed, HINARI, EMBASE, Google Scholar and African Journals), other gray and online repository accessed studies were searched using different search engines. Newcastle-Ottawa Quality Assessment Scale (NOS) was used for critical appraisal of studies. The analysis was done using STATA 11 software. The Cochran Q test and I(2) test statistics were used to test the heterogeneity of studies. The funnel plot and Egger’s test were used to detect publication bias of the studies. The pooled prevalence of perinatal asphyxia and the odds ratio (OR) with a 95% confidence interval was presented using forest plots. RESULT: Nine studies were included in this review, with a total of 12,249 live births in Ethiopia. The overall pooled prevalence of perinatal asphyxia in Ethiopia was 24.06% (95 95%CI: 18.11–30.01). Associated factors of perinatal asphyxia included prolonged labor (OR = 2.79, 95% CI: 1.98, 3.93), low birth weight (OR = 6.52, 95% CI: 4.40, 9.65), meconium-stained amniotic fluid (OR = 5.91, 95% CI: 3.95, 8.83) and instrumental delivery (OR = 4.04, 95% CI: 2.48, 6.60) were the determinant factors of perinatal asphyxia in Ethiopia. CONCLUSIONS: The overall pooled prevalence of perinatal asphyxia was remarkably high. Duration of labor, meconium-stained amniotic fluid, instrumental deliveries, and birth weight were the associated factors of perinatal asphyxia in Ethiopia. Therefore, efforts should be made to improve the quality of intrapartum care service to prevent prolonged labor and fetal complications and to identify and make a strict follow up of mothers with meconium-stained amniotic fluid. This finding is important to early recognition and management of its contributing factors, might modify hypoxic-ischemic encephalopathy and may improve the implementation of the standard guideline effectively and consistently.